CEO Tenure and Financing Decisions of Nigerian Non-Financial Listed Firms: A Dynamic Panel Approach - Sani, Abdullahi (Journal of Accounting, Business and Finance Research, 2020)
Access to long-term debt has been a persistent problem facing Nigerian non-financial listed firms. The existing literature suggests that CEO tenure has a bearing on the ability of firms to secure a considerable amount of borrowings to finance their investment opportunities. However, Nigeria’s corporate governance framework does not contain a specific recommendation on the CEO tenure, which in turn results in an unstable tenure of CEOs in the Nigerian corporate environment. Thus, this paper examines how CEO tenure influences the financing pattern of the companies operating in the country. The study analysed the balanced panel data set of 63 Nigerian listed firms for seven years (2012- 2018) using the two-step system GMM. In particular, the research found that CEO tenure is significantly and positively associated with the firms’ leverage ratio. This evidence underscores the relevance of the CEO tenure on the borrowing decisions of the Nigerian non-financial listed firms. The findings of this research have some policy implications on the firms’ capital structure choices. First of all, the Nigerian firms should attach more value to the longer serving CEOs, because longer tenure enhances CEOs’ strategic decisions, including the choice of optimum leverage. Also, regulatory authorities in Nigeria should specify the number of years CEOs should serve. By doing so, CEOs will have a stable term in office and thereby empowering them in collaboration with their board members to design an effective debt policy to boost the firms’ value.